HAMBATAN-HAMBATAN GURU MATA PELAJARAN IPS DALAM MENERAPKAN KURIKULUM 2013 PADA PROSES PEMBELAJARAN DI SMA NEGERI 1 MANDAU KABUPATEN BENGKALIS KELURAHAN TALANG MANDI - DURI - Putra, Ade Agus (Pendidikan Sosiologi, 2014)
The research about implementation as well as the barriers that find by teachers in implementing curriculum 2013. The purpose of this research is to describe how the implementation and the barriers that find by teachers in implementing curriculum 2013 on the learning process. This research utilize qualitativeâs approach with type of descriptive. Techniques of data collection with three ways: namely interviews, observation, and documentation while analysis of data through four steps : data collection, data reduction, data display and conclusion. The result of this research can be concluded that the implementation of curriculum 2013 in SMAN 1 Mandau began in July 2013 to 2014 school year, in implementing curriculum 2013, teacher sued to preparation as well as attending various training, beside that teacher also preparation lesson plans, semester program until yearly program. The barriers that find by teachers in implementing curriculum 2013 consist of: (1) The barriers in preparing lesson plans (2) barriers to use learning strategies (3) barriers to use learning methods (4) barriers to using learning media.